Aplikasi Konsultasi Gizi Berbasis Android - Bakhrul Na'im Irawan; Nia Saurina (Melek IT : Information Technology Journal, 2017)
The role of nutrition in improving the intelligence does not stop when a two-year-old man. The occurrence of nutritional problems due to the mismatch between intake of nutrients the body needs. Information about nutrition is very important for the community. The lack of public knowledge about the importance of nutrition and nutritional information about due to the lack of understanding of where the public to obtain information about nutrition.When citizen know that their complaints about nutrition can only be consulted to the doctor because of the role of the dietitian is not yet well known by the public at large. The nearest communication media is currently the Smartphones, where smartphones can reach a community communication much easier. Therefore this research makes nutrition consulting Android-based applications that can be aimed to help the Community (patients) consultation directly without hampered time and distance with a nutritionist